Determinants of sputum smear nonconversion in smear-positive pulmonary tuberculosis patients in Suriname, 2010 - 2015 - Eric Commiesie; Deborah Stijnberg; Diana Marín; Freddy Perez; Mauro Sanchez (Pan American Health Organization, 2019)
Objective. To identify factors associated with sputum smear nonconversion in patients with pulmonary tuberculosis (PTB) in Suriname. Methods. A case-control study was conducted using routinely-collected surveillance data of PTB cases reported in January 2010 - December 2015 and recorded in the database of the National Tuberculosis Program of Suriname. Cases were smear-positive PTB patients whose sputum results were negative 2 months after treatment initiation. Controls were the smear-positive PTB patients whose sputum results were negative in the same timeframe. Multivariate logistic regression analysis was used to examine associations between potential risk factors and smear conversion. Results. The two age groups ≥ 35 years (35 - 54 years, AOR: 2.7, 95%CI: 1.2 - 6.1; and 55+ years, AOR: 2.5, 95%CI: 1.1 - 5.9) and high bacillary load at baseline (AOR 2.34, 95%CI: 1.2 - 4.8) were significantly associated with delayed smear conversion. Conclusion. The National TB program of Suriname should develop strategies to address patients at higher risk for delayed smear conversion to prevent further spreading and unfavorable treatment outcomes. To better inform decision-making and future studies, the NTP should expand its data collection to include all risk factors for delayed smear conversion.